Une hypothèse connexionniste sur la métrique orale - Floquet, Oreste (Cognitive philology, 2009)
In this paper we present a connectionist, quasi-phonetic, approach to some French nursery rhymes and slogans. We propose to model the intrinsic structure variation of this kind of texts, using a subsymbolic representation (the Laksian “courbe rythmique”). We try to demonstrate that feet are not primitives (but they are the by-product of the integration process of the alternation of stresses and the text alignement), and that a verse-based approach (in which the musical syntax always coincide with the metrical one) fail to explain the 3-4 beat texts as Am stram gram.